Studies on certain aspects of prevalence of Culicoides species - REDDY, C V SUBBA; HAFEEZ, Md. (The Indian Journal of Animal Sciences, 2011)
This present experiment was conducted to study the prevalence of Culicoides species in Chittoor and Prakasam districts ofAndhra Pradesh, recording the animal-wise, sex-wise and age-wise occurrence of Culicoides species besides the role of Culicoides species in the transmission of the diseases if any. Out of 100 light trap attempts only in 52 light traps Culicoides spp could be captured in the areas where bluetongue disease was endemic from 2001 to 2003, and 1297 Culicoides midges were collected. Out of these 982(75.7%) were identified as female Culicoides and 315 (24.3%) as male species. Flies (1359) were collected during the period by both light traps and aspirators. Out of these 1297 flies were collected by using light traps and 62 by aspirators. C.actoni, C.anophelis, C.inoxius, C.majorinus, C. oxystoma and C. perigrinus were present in catches from April to August 2004. Among the 6 spp. identified, C.oxystoma was the predomin~t species in number and the least was C.perigrinus.Â